Introduction to Qiyas and Maslahah Mursalah and Its Application In The Future - Remiswal Remiswal; Ayu Angraini; Asma Boti; Zerly Nazar (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2021)
This paper discusses  qiyas and maslahah mursalah. The goal is to make it easier for us to establish a law. The data collection method that the writer uses is a literature study in the form of searching for books related to qiyas and  maslahah  mursalah. Qiyas In language (Arabic) means measuring, knowing the size of something,  comparing, or equating something with another. For example  قمت اللوب بالنراع which means "I  measure  clothes  in cubits." According to Ushul Fiqh terminology, as stated by  Wahbah al-Zuhaili, qiyas is connecting or equating the Law of something with no legal provisions with legal provisions there is  Illat similarity between the two. The meaning of  Maslahah in  Arabic means "actions that encourage human goodness." This article uses the induction and deduction methods and the descriptive analysis approach by conducting a literature study. The result shows that Allah decreed all the laws to his servants in orders/prohibitions containing Maslahah and benefits. The specialty of this paper is that it is written in detail based on arguments so that it is easy to understand. Qiyas and maslahah mursalah are very important for us to understand more deeply to determine an appropriate law. Maslahan Mursalah is an extension of qiyas if there are no more arguments that can support  qiyas.Artikel ini membahas tentang qiyas dan maslahah mursalah. Tujuannya untuk memudahkan dalam membuat undang-undang. Metode pengumpulan data yang digunakan adalah studi kepustakaan berupa pencarian kitab-kitab yang berhubungan dengan qiyas dan maslahah mursalah. Qiyas dalam bahasa (Arab) berarti mengukur, mengetahui ukuran sesuatu, membandingkan, atau menyamakan sesuatu dengan yang lain. Misalnya اللوب بالنراع yang artinya "Aku mengukur pakaian dalam hasta". Menurut istilah Ushulfiqh, sebagaimana dikemukakan oleh Wahbah al-Zuhaili, qiyas adalah menghubungkan atau menyamakan hukum sesuatu yang tidak ada ketentuan hukumnya dengan ketentuan hukumnya terdapat kesamaan illat antara keduanya. Arti Maslahah dalam bahasa Arab berarti “perbuatan -perbuatan yang mendorong kebaikan manusia”. Artikel ini menggunakan metode induksi dan deduksi serta pendekatan analisis deskriptif dengan melakukan studi kepustakaan. Hasil penelitian ini menunjukkan bahwa Allah menetapkan segala hukum kepada hamba-hamba-Nya dalam perintah/larangan yang mengandung maslahah dan kemaslahatan. Keistimewaan makalah ini adalah penulisannya secara detail berdasarkan argumentasi sehingga mudah dipahami. Qiyas dan Maslahah Mursalah sangat penting untuk dipahami lebih dalam untuk menentukan hukum yang tepat. Maslahan Mursalah merupakan perpanjangan dari qiyas jika tidak ada lagi dalil yang dapat mendukung qiyas.